Effect of silkworm (Bombyx mori L.) pupae oil dietary inclusion on growth performance, digestibility and carcase traits of growing rabbits - Marco Cullere; Zsolt Szendrő; Zsolt Matics; Zsolt Gerencsér; Yazavinder Singh; Antonella Dalle Zotte (Italian Journal of Animal Science)
The study aimed to evaluate the effect of the dietary inclusion of silkworm (Bombyx mori) oil (SWO) in rabbit diets as a total replacement of sunflower oil on growth performance, carcase traits, total tract apparent digestibility (TTAD) and nutritive value of the diets. A total of n = 64 mixed-sex weaned rabbits (5-week-old) were pair-housed in cages and fed with a commercial diet containing 1.3% sunflower oil (control). From 7 to 10 weeks of age, two experimental groups were formed: half of the rabbits received a control diet, and the other half received a diet where the sunflower oil was replaced by the SWO. During the trial, growth parameters and feed intake were weekly recorded to calculate productive parameters. At 10 weeks of age, rabbits were slaughtered and dissected to determine carcase traits. In parallel to the growth trial, another twenty-four 55-day-old rabbits were individually housed in digestibility cages and randomly assigned to one of the two experimental groups (n = 12 rabbits/group) to study the TTAD and nutritive value of the diets. Overall, the dietary inclusion of SWO did not affect the in vivo performance and carcase traits of rabbits. Additionally, the TTAD of rabbits was unaffected by SWO inclusion, although the SWO diet exhibited lower digestible energy (DE) compared to the control diet (p < .05). These findings emphasise the importance of further investigating the nutritive value of SWO-supplemented diets in future studies. In conclusion, SWO can be considered a promising energy source for growing rabbits, an alternative to conventional vegetable oils.